THE SCIENTIFIC-THEORETICAL FOUNDATIONS OF USING ARTIFICIAL INTELLIGENCE-BASED BLENDED LEARNING METHOD (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
his article explores the scientific-theoretical foundations of using AI-based blended learning, highlighting its pedagogical value, technological underpinnings, and practical applications in modern classrooms.This hybrid approach has proven to be highly effective, especially in language learning and h